Perencanaan Strategi Pemasaran Pada UMKM Warung Pecel Lele Bejo - Rimadias, Santi; Januar, Ahmad; Savira, Izky; Mawarni, Nor Anisa; Wulandari, Ratih; Onari, Priscilla Yen (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the economy, playing a key role in community development and making a significant contribution to economic growth. MSMEs hold a strategic position in accelerating structural transformation and improving people's living standards. MSMEs contribute by creating job opportunities, encouraging sustainable economic growth, and encouraging income equity. This research focuses on the analysis of marketing strategy planning in Warung Pecel Lele Bejo SMEs to increase their competitiveness and ensure business sustainability. A mixed-methods approach, which combines observation, in-depth interviews, and SWOT analysis, is used. The findings highlight opportunities for growth, particularly through enhanced marketing strategies, and underscore the importance of leveraging digital tools to enhance competitiveness and support sustainable economic progress